THE PREVALENCE OF FURUNCULOSIS AND PLASMID MEDIATED RESISTANCE OF ISOLATES OFSTAPHYLOCOCCUS AUREUS FROM INFECTED INDIVIDUALS IN SOUTHWEST NIGERIA. (2012)
Furunculosis, a cosmopolitan infection of human skin caused by Staphylococcus aureus, is recurrent among most infected individuals. It is characterized by a honey crusted "cropped" latent boil with potential to recur in a susceptible host. It is a common colonizer of the skin with a remarkable ability to hydrolyse ?-lactam antibiotics, degrade skin lipid barrier and spread within the skin loci. In this study, the gender and age distributions of furunculosis, the antibiotic susceptibility pattern of its causative agent and the genetic basis of the recurrency were determined. Exudates of "cropped-boils" were obtained from 140 human volunteers (40 hospital reported and 100 non-reported cases of recurrent furunculosis) from different age range(1-100 years) for both genders within the six southwest states of Nigeria. The exudates were processed for isolation and identification of S. aureus by selective plating and biochemical tests. Antibiogram of the isolates was determined by disc-diffusion using multi-discs of eight standard antibiotics. Minimum Inhibitory Concentrations (MIC) of five selected antibiotics: amoxicillin-clavulanic acid, penicillin, ceftriaxone, cefuroxime and cloxacillin were determined by broth-dilution method. Detection of ?-lactamase was carried out by cell-suspension iodometric method. Positive strains were processed for plasmid DNA isolation and molecular weight determination by lystostaphin cell lysis and agarose gel electrophoresis. Curing of R-plasmid DNA in selected bacterial strains was done by exposure to ethidium bromide prepared in 2-fold dilutions in nutrient broth from 6.25-100.00 μg/mL. Transfer of resistance was done by conjugation between some resistant strains as donors and Carolina-typed sensitive E. coli; E. coli 01 and E. coli 02 strains as recipients. The data were analysed using ANOVA at p = 0.05. A total of 102 isolates comprising seventeen from each of the six southwest states were identified and selected. The gender distributions were 46.0% females and 54.0% males, comprising of 20.0% hospital reported and 80.0% non-reported for the highest prevalence females and 5.0% hospital reported and 95.0% non-reported for males. Recurrent furunculosis had the highest prevalence in males within the age groups 11-50 years and in females, age groups, 11-70 years. The isolates exhibited the lowest resistance of 8.0% to amoxicillin-clavulanic acid and 95.0% as the highest resistance to amoxicillin. Thirty of the isolates possessed ?-lactamase in varying degrees out of which 29.0 were plasmid-borne. Of this number, 7.0 had multiple plasmid DNA of 2- 4 copies, ranging between 0.25 and 63.09 kb. The MIC of the antibiotics showed that the isolates were most susceptible to amoxicillin-clavulanic acid ( 3.90 - 250 μg/mL) and the highest resistance was recorded for penicillin G (7.8 - 500 μg/mL). Curing of R-plasmid DNA occurred at concentrations of 50.0μg/mL and 100.0μg/mL of ethidium bromide while conjugation was achieved in two out of seven competent cells, indicating a plasmid-borne resistance. The prevalence of furunculosis varied across the different age groups. The high level multidrug resistance elicited by the strains of Staphylococcus aureus isolated was established to be due to the associated transferable R-plasmid encoded ?-lactamase.